Changes in flavour compound profiles of precooked pork after reheating (warmed‐over flavour) using gas chromatography–olfactometry–mass spectrometry with chromatographic feature extraction. (10th October 2019) - Zang, Mingwu; Wang, Lan; Zhang, Zheqi; Zhang, Kaihua; Li, Dan; Li, Xiaoman; Wang, Shouwei; Chen, Hongzhang
Summary: The unclear components and complex evaluation indicators affect the effectiveness of inhibition methods for warmed‐over flavour (WOF). To evaluate the main components of WOF, the changes in flavour compound profiles of precooked pork after reheating were investigated quantitatively by using gas chromatography–olfactometry–mass spectrometry with chromatographic feature extraction. A total of 49 volatile compounds were identified, including 22 aroma‐active compounds that were primarily derived from lipid oxidation. Fifteen key volatile compounds were obtained that represented principal components of the changes in flavour compound profiles, of which 1‐octen‐3‐ol, ( Z )‐2‐octenal and ( E, E )‐2, 4‐decadienal made the greatest contribution to the principal components and achieved odour activity value (OAVs) >1.0 after reheating. The results showed that the three compounds are the dominant volatile compounds and potential evaluation indicators of WOF. This study provides a further understanding of the components of WOF in precooked pork and an effective analysis method of gas chromatography. Abstract : Changes in flavour compound profiles of precooked pork after reheating were investigated quantitatively by using gas chromatography–olfactometry–mass spectrometry with an effective analysis method of chromatographic feature extraction, which showed that 1‐octen‐3‐ol, (Z)‐2‐octenal, and (E, E)‐2, 4‐decadienal were the dominant volatile compounds and potential evaluation indicators of warmed‐over flavour.